Antibacterial Effectiveness Test of Potato Peel Ethanol Extract (Solanum tuberosum L.) against Lactobacillus acidophilus: An In Vitro Study - Aurelia Krisnadita; Endang Sri Lestari; Aris Setyawan; Arlita Leniseptaria Antari (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Lactobacillus acidophilus is one of the bacteria that play a major role in the caries process. It is recommended to use cavity cleanser to clean and disinfect caries cavities post-preparation. However, the currently used cavity cleansers, 2% chlorhexidine digluconate and sodium hypochlorite, have limitations. Thus, exploring natural alternatives, like potato peel, as a cavity cleanser material is necessary. This study aims to determine the antibacterial effectiveness of the ethanol extract of potato peel (S. tuberosum L.) on the growth of L. acidophilus. The method used was true experimental laboratories with a post-test-only control group design and broth dilution. The samples were divided into 8 groups, including 6 treatment groups with varying concentrations of extract (100%; 50%; 25%; 12.5%; 6.25%; and 3.125%), positive control, and negative control. Each group was repeated 4 times. The Minimum Inhibitory Concentration (MIC) was determined by observing solution turbidity in the tubes which began to appear clear after 24 hours of incubation, while the Minimum Bactericidal Concentration (MBC) was determined by the absence of bacteria that grew on media after being given the test solution and incubated for 24 hours. The MIC of potato peel ethanol extract on the growth of L. acidophilus could not be determined, while the MBC was at a concentration of 50%. The Kruskal-Wallis test showed that concentration levels had a significant difference in the average number of L. acidophilus colonies. The ethanol extract of potato peel (S. tuberosum L.) has antibacterial effectiveness against the growth of L. acidophilus.